Macromedia Flash 8 for Dummies - Finkelstein, Ellen (Wiley Publishing, 2011)
Make the Web interactive with your own animations Liven up your Web site with graphics that move, buttons that light up, and more Flash is fun - and this book makes it easy whether you're using a Mac(r) or Windows(r). Fill letters with images, create buttons that glow or change color when you pass your mouse over them, play video and sound files, morph objects into different ones, and do dozens of other things to make your site flashier. Discover how to * Create animated text * Find sample Flash files * Explore links to additional information * Add sound and video * Build great user interfaces * Publish your Flash files